Research on the Development of Modern Computer Technology in the Field of Law — Based on Big Data and Community Correction Supervision. Issue 4 (October 2020) - Liu, Zexin
Abstract: At present, the community correction based on big data has entered the comprehensive pilot trial stage, but also faces a series of practical problems, such as lack of legal basis, unclear subject of implementation, small number of applicable objects and narrow scope. The application of modern computer technology in the field of law is extensive and far-reaching. Based on the current situation of community correction based on big data in China, this paper discusses some shallow understanding and Suggestions on how to solve the problems and difficulties encountered by procuratorial organs in participating in community correction based on big data.